Student Assessment On Private University Business Office Service Quality - Matindas, Ernest Cornelius; Pangemanan, Anthony Stafford (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
In universities, there are several supporting departments other than faculties that are often visited by students, one of which is the department that handles student finance. This study aims to understand the quality level of services received by students provided by the support departments related to student finance in private tertiary institutions, namely the Business Office department, and to comprehend what service improvements can be recommended to the institution. Service dimensions used to measure the service quality are based on SERVQUAL, which consists of reliability, assurance, tangibility, empathy, and responsiveness to sort out the services that should be maintained and improved. Researchers used the Importance-Performance Analysis from Martila and James. Samples were obtained from 209 respondents, and a T-test of pair sample was used to test the existence of a gap between expectation and serviced perceived. The test found there is a gap between the average performance with the average expectations with a significant p-value = 0.000. The conclusion is there are differences in the level of service expected by students with the level of services provided by the business office, and the variables that can be improved by the Business Office are work employees’ dexterity, sympathy and sincerity to students, understanding, and employees willingness to help students. Keywords : Importance-Performance Analysis, Satisfaction, Service department, Service perceived, SERVQUAL